23S rRNA from Vibrio parahaemolyticus regulates the innate immune response via recognition by TLR13 in orange-spotted grouper (Epinephelus coioides). (January 2021) - Yu, Xue; Liang, Yaosi; Zhou, Ying; He, Liangge; Liu, Yuqi; Fu, Lijun; Lin, Haoran; Zhang, Yong; Lu, Danqi
Abstract: Toll-like receptors (TLRs) are major pattern recognition receptors (PRRs) that recognize multiple pathogen-associated molecular patterns (PAMPs) through the leucine-rich repeat (LRR) domain and mount effective immune responses. Vibrio parahaemolyticus is the main pathogen that causes vibriosis in aquatic animals, yet the mechanisms of its recognition by innate immune system in teleost fish remain unknown. Here, the results reveal that TLR13 in orange-spotted grouper ( Epinephelus coioides ) ( Ec TLR13) recognizes a conserved 23S ribosomal RNA (23S rRNA) sequence in V. parahaemolyticus, and the 13-nucleotide motif near the 23S rRNA ribozyme activation site (VP13) acts as a PAMP. After challenge with RNA and 23S rRNA from V. parahaemolyticus and with the synthetic oligoribonucleotide VP13, the expression of Ec TLR13 in grouper spleen cells (GS cells) was significantly increased. Ec TLR13-knockdowned GS cells were stimulated with the same stimulants as listed above, the expression of IL-6, IL-12, IL-1β and TNFα was significantly reduced. RNA-protein immunoprecipitation revealed that VP13 could directly bind to Ec TLR13. The dual-luciferase reporter assay also showed that Ec TLR13 enhanced the fluorescence activity of IFNβ rather than that of NF-κB when the cells were challenged with RNA from V. parahaemolyticus or with synthetic VP13. Our study established the mechanism of fish TLR13-mediated recognition of microbial products during V. parahaemolyticus infection. Highlights: The binding mechanism between fish TLR13 and its specific ligand was determined. After TLR13 was knocked down, the TLR13-triggered expression of cytokines was suppressed. Ec TLR13 activated the type I interferon pathway in the immune response to Vibrio parahaemolyticus.